The Influence Of Islamic Leadership On Teacher Performance In Islamic Educational Institutions: A Systematic Literature Review - Sri Hartono (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to explore the influence of Islamic leadership on teacher performance in Islamic educational institutions through the Systematic Literature Review (SLR) approach. A total of 45 articles from journals published between 2012 and 2022 have been identified, and after going through a screening process, 20 relevant articles were reviewed in depth. The review results show that Islamic leadership, which is based on the values of honesty, justice, and example, positively affects teacher performance. Factors such as leader example, moral support, and participatory communication are essential in improving teacher motivation and performance. However, it was found that the influence of Islamic leadership on teacher performance can be limited if organizational policies and a conducive work environment do not support it. The study also identified research gaps related to the specific relationship between Islamic leadership and teacher performance and a lack of exploration of moderation and mediation factors that affect these relationships. This research provides practical implications for managers of Islamic educational institutions to be more consistent in applying Islamic values in leadership and the importance of providing a work environment that supports teachers' professional development. Thus, this research contributes to a deeper understanding of the dynamics of Islamic leadership and teacher performance and opens up opportunities for more targeted follow-up research.